Down-regulation of miRNA-196b expression inhibits the proliferation, migration and invasiveness of HepG2 cells while promoting their apoptosis via the PI3K/Akt signaling pathway - Xu, Fanggui; Zhu, Feng; Wang, Wulin; Gao, Wenjie; Chen, Xin; Yu, Chunzhao (Cellular and Molecular Biology, 2020)
The purpose of this study was to investigate the effects of microRNA-196b (miRNA-196b) on proliferation, migration, invasiveness and apoptosis of hepatocellular carcinoma cell line (HepG2), and the mechanism involved. MiRNA-196b inhibitor or negative control were transfected into HepG2 cells, while empty liposome vector was used as normal control. The results of transfection were assessed using real-time quantitative polymerase chain reaction (qRT-PCR). Cell proliferation, migration, invasiveness and apoptosis were determined using cell counting kit 8 (CCK-8), scratch test, Transwell invasion assay, and flow cytometric analysis, respectively. The expressions of PIK3, Akt and p-Akt proteins were determined using Western blotting. The HepG2 cells were also treated with PI3K/Akt signaling pathway inhibitor LY294002, and its effect on cell proliferation, migration, invasion, and apoptosis, and expressions of PIK3, Akt, and p-Akt proteins were determined. The results of RT-PCR showed that the relative expression of miRNA-196b in the inhibitor group (0.42 ± 0.13) was significantly lower than that in the blank control group (0.96 ± 0.10) and the negative control group (1.01 ± 0.32) (p < 0.05). The miRNA-196b inhibitor significantly and time-dependently reduced the invasiveness, proliferation migration abilities of HepG2 cells, while promoting their apoptosis (p < 0.05). The expressions of PIK3 and p-Akt proteins were significantly down-regulated in the inhibitor group, when compared with normal and negative control groups (p < 0.05). However, there were no significant differences in the expression of Akt protein among the groups (p > 0.05). After treatment of HepG2 cells with PI3K/Akt signaling pathway inhibitor LY294002, the proliferative, migratory and invasive abilities of cells in the treatment group were significantly enhanced, while cell apoptosis was significantly reduced (p < 0.05). Similarly, the protein expressions of PIK3 and p-Akt in the non-treatment group was significantly upregulated, relative to the treatment group (p < 0.05), but there was no significant difference in the expression of Akt protein between the two groups (p > 0.05). Downregulation of miRNA-196b expression inhibits the proliferation, migration and invasiveness of HepG2 cells, while promoting their apoptosis via a mechanism involving the PI3K/Akt signaling pathway.